The IDB's first decade and perspectives for the future; [proceedings of the] Round Table, Inter-American Development Bank, Punta del Este, Uruguay, April 1970. - Inter-American Development Bank. ([n.p., 1971)
This book contain discussions held in Punta del este on the need to examine self-analysis of the working of Inter-American Development Bank (IDB) for first ten years and projected its activity into the 1970s.
asm; 13/02/19
Loans
Keywords: Latin America